2010
DOI: 10.1074/jbc.m109.041640
|View full text |Cite
|
Sign up to set email alerts
|

NFκB p50-CCAAT/Enhancer-binding Protein β (C/EBPβ)-mediated Transcriptional Repression of MicroRNA let-7i following Microbial Infection

Abstract: MicroRNAs, central players of numerous cellular processes, regulate mRNA stability or translational efficiency. Although these molecular events are established, the mechanisms regulating microRNA function and expression remain largely unknown. The microRNA let-7i regulates Toll-like receptor 4 expression. Here, we identify a novel transcriptional mechanism induced by the protozoan parasite Cryptosporidium parvum and Gram(؊) bacteria-derived lipopolysaccharide (LPS) mediating let-7i promoter silencing in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
82
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 29 publications
3
82
0
Order By: Relevance
“…The let-7 family is known to orchestrate a role in cellular proliferation and the innate immune response (8,12,50). In our study, let-7i expression across the groups is significantly altered, and the expression is significantly increased in PbAinfected CBA mice versus that in NI mice (P Ͻ 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 53%
“…The let-7 family is known to orchestrate a role in cellular proliferation and the innate immune response (8,12,50). In our study, let-7i expression across the groups is significantly altered, and the expression is significantly increased in PbAinfected CBA mice versus that in NI mice (P Ͻ 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 53%
“…It is involved in both transcriptional activation and suppression, and recent evidence has implicated C/EBPb in the transcriptional silencing of miRNAs such as let-7i, miR-145, and miR-155 (53,63). Accessibility of promoters to C/EBPb depends on H3 methylation status at the C/EBPb binding region, as demonstrated previously (64,65).…”
Section: Discussionmentioning
confidence: 54%
“…In previous studies, the let-7 gene family in mammals have been reported to regulate the expression of major cytokine-inducible proteins in immune response against microbial infection (O'Hara et al, 2010;Asgari, 2011;Schulte et al, 2011;Asgari, 2012). In this study, Let-7 was predicted to be involved in the regulation of some important sex-determination-related genes of M. nipponense.…”
Section: Discussionmentioning
confidence: 71%